Differential expression of salivary S100A7 in oral submucous fibrosis - Muhammad Arsalan Raffat; Naila Irum Hadi; Mervyn Hosein; Adnan Mustafa Zubairi; Sana Ikram; Zohaib Akram (Saudi Dental Journal)
Aim: To investigate the expression of salivary S100A7 levels among patients with oral submucous fibrosis (OSF) and healthy controls. Method: A total number of 60 participants were included in the study (30 OSF cases and 30 healthy controls). Demographic data was collected using a structured baseline questionnaire. Salivary S100A7 levels were quantified using enzyme-linked immunosorbent assay. Data was analyzed using Student t-test. Pearson correlation test was used to evaluate correlation between S100A7 levels and independent variables such as frequency and duration of areca nut use, gutka use, and mouth opening. Results: The mean value of salivary S100A7 for OSF group was 0.275 ng/ml, whereas mean value of salivary S100A7 for healthy controls was 0.195 ng/ml. Student t-test indicated that there was statistically significantly higher levels of S100A7 in OSF group as compared to healthy controls (p < .001). When the clinical variables of individual groups were analysed, a significant negative correlation was found between salivary S100A7 and duration of areca nut (p = .009) and gutka chewing (p = .03), whereas a significant positive correlation was found for mouth opening (p = .04). Conclusion: OSF presented higher levels of salivary S100A7 levels as compared with healthy individuals and may be used as surrogate measure to identify subjects at risk for OSF. Keywords: Oral submucous fibrosis, Saliva, S100A7 protein